Assessment of blood pressure and lipid profile in 1–5 years stunted children attending a tertiary care hospital - Deka, Anupama; Barman, Diganta; Ray, Prajnan Sankar (Indian Journal of Child Health, 2020)
Introduction: The prevalence of coronary artery disease (CAD) is rapidly increasing worldwide, particularly affecting low- and middle-income countries with high burden of malnutrition. Childhood stunting signifies chronic undernutrition in early life. There is an increased risk of metabolic alterations, namely, poor glycemic control, hypertension, and altered lipid profile that occur in children with stature deficit. Long-term effect of these metabolic alterations may predispose these undernourished children to an increased risk of CAD in future life. Aim: This study aims to assess the blood pressure (BP) and lipid profile in stunted children in the age group of 1–5 years. Materials and Methods: The present study was conducted in a tertiary care hospital in eastern region of India. The study comprised 65 stunted children (with height for age [HFA]